FRI0055 Ectopic calcification is mediated by inflammatory cytokines enhancing differentiation of adipose-derived stem cells into osteoblasts. (23rd January 2014) - Fukuyo, S.; Yamaoka, K.; Sonomoto, K.; Oshita, K.; Okada, Y.; Saito, K.; Tanaka, Y.
Abstract : Background: Although ectopic cutaneous calcification is occasionally observed in connective tissue disease such as juvenile dermatomyositis (JDM), causing multiple complications, its mechanism remains unclear. Recent reports have suggested the involvement of mesenchymal stem cells in the pathological processes of autoimmune disease. Therefore, depending on the discriminative localization of calcification and inflammation due to JDM, we have assessed the involvement of adipose tissue-derived stem cells (ADSCs) in ectopic calcification. Objectives: Aim of this study was to assess the involvement of ADSC in ectopic cutaneous calcification. Methods: Human ADSCs were cultured in the commercialized osteogenic induction medium (OIM) with or without IL-6/sIL-6 receptor, tumor necrosis factorα (TNFα) or IL-1β. Differentiation to osteoblasts was detected by alkaline phosphatase-staining, real-time PCR and western blotting of osteoblastic markers. Mineralization was assessed by alizarin red S stain. Transcription factors Stat1 and Stat3 were evaluated by western blotting and inhibited with small interfering (si) RNA. Expression of IL-6 and RUNX2 at the ectopic calcification region from a JDM patient was analyzed by immunohistochemistry. Results: Addition of inflammatory cytokines to OIM enhanced ALP-staining at day 5 and calcifications at day 8 in a dose-dependent manner (0-100ng/ml), whereas 14 days were necessary for calcification with OIM alone. Among the evaluated cytokines, IL-6/sIL-6R (100ng/ml) most efficiently increased expression of RUNX2, a master gene of osteoblastogenesis within 24 hours and further magnified at day8 resulting in enhanced osteoblast differentiation. Although it is known that Wnt pathway is heavily involved in osteoblastogenesis, canonical pathway mediated by suppression of b-catenin degradation was not altered by the addition of IL-6/sIL-6R. Contrarily, IL-6/sIL-6R strongly increased Ror2 expression, a receptor utilized in non-canonical pathway in 24 hours. Inhibition of IL-6 signaling with Stat3 siRNA apparently suppressed RUNX2, Ror2 expression and calcification, whereas Stat1 siRNA did not show any effects. Additionally, Ror2 siRNA prominently suppressed calcification. Finally, calcified cutaneous tissue obtained from a JDM patient showed positive staining with IL-6 and RUNX2 specific antibodies. Conclusions: Our results indicate for the first time the involvement of ADSC in ectopic calcification through the activation of Wnt non-canonical pathway by IL-6 in JDM patients. The enhanced calcification was dependent on Stat3 activated by IL-6. The presence of Stat-binding cites in the Ror2-promoter region suggests that the activated Stat3 positively regulating Ror2 expression and differentiation and mineralization of ADSC. Moreover, our results suggest the involvement of ADSC in the homeostasis of adipose tissue that requires Stat3. Disclosure of Interest: S. Fukuyo: None Declared, K. yamaoka: None Declared, K. sonomoto: None Declared, K. oshita: None Declared, Y. okada: None Declared, K. saito: None Declared, Y. tanaka Consultant for: Tanabe Pharma, Pfizer Inc., Speakers Bureau: Mitsubishi-Tanabe Pharma, Takeda Pharmaceutical Co Ltd, Abbott, Eisai Pharma, Chugai Pharma